Large eddy simulation of n-heptane/syngas pilot ignition spray combustion: Ignition process, liftoff evolution and pollutant emissions. (15th October 2021) - Zhong, Shenghui; Xu, Shijie; Bai, Xue-Song; Peng, Zhijun; Zhang, Fan
Abstract: The utilization of syngas in the internal combustion engine is one way to reach low carbon emission engine. The n-heptane/syngas pilot ignition spray combustion is simulated here by high fidelity model with different syngas compositions. It is found that the ambient syngas suppresses the ignition by diluting the ambient oxidizer (non-chemical effect) and by affecting the chemical reactions (chemical effect). The consumption of OH radicals through H2 +OH = H + H2 O and CO + OH = CO2 +H in low temperature combustion (LTC) stage is shown to be the main reason for the suppression of ignition. Cool flame propagation into the rich mixture in the mixing layer of n-heptane jet is observed during the transition process from LTC to high temperature combustion (HTC). CO is found to assist the transition to HTC through CO + HO2  = CO2 +OH. On the contrary, H2 slows down the cool flame propagation and narrows down the cool flame flammability range, which retards the onset of HTC. The effects of syngas compositions on the flame structure and emission formation are discussed in detail. Due to the upstream auto-ignition, a cool/diffusion/hot flame structure is identified at the liftoff position in dual-fuel case, which drastically changes the flame structure. And more soot formation in early stage is found in dual-fuel cases due to the naturally richer mixture. Highlights: N-heptane/syngas pilot ignition spray combustion under engine conditions are studied using LES and transported PDF model. Syngas affects the low temperature ignition by diluting ambient oxidizer and depleting the OH radicals. The chemical effect of H2 on spray ignition is more significant than that of CO. New cool flame involved triple-flame is found in dual-fuel combustion. Hydrogen in syngas promotes NOx emission but suppresses soot emission.